IMPACT OF BLOCKCHAIN TECHNOLOGY APPLICATIONS ON THE EFFICIENCY AND PERFORMANCE OF COMPANIES - Antanasković, Dejan (ACADEMIC REVIEW, 2025)
Pervasive ICT, the knowledge economy, and intense global competition define the business landscape in the 21st century. Long-term sustainability for companies hinges on continuously boosting competitiveness through increased efficiency and profitability. This paper explores how Blockchain technology influences management quality, reduces operating costs, and enhances overall competitiveness. Initially known for cryptocurrencies like Bitcoin, Blockchain is now increasingly vital for improving business and management efficiency. Through extensive research, the authors found that decentralization, transparency, and enhanced security — core benefits of Blockchain — significantly improve decision-making across all management levels and optimize business processes. The ultimate outcomes are reduced costs, greater operational efficiency, increased profitability, and sustainable development. Therefore, Blockchain technology is a crucial factor shaping future management and business practices in our dynamic global environment.